mySmartCart: a smart shopping list for day-to-day supplies - Sowmya Kyathanahalli Nanjappa; Sowmya Prakash; Aiswarya Burle; Nandish Nagabhushan; Chaitanya Shashi Kumar (Institute of Advanced Engineering and Science, 2023)
Shopping of day-to-day items and keeping track of the shopping list can be a tedious and a time-consuming procedure, especially if it has to be done frequently. mySmartCart is a mobile application design proposed to transform the traditional way of writing a shopping list to a digitalized smart list which implements voice recognition and handwriting recognition for processing the natural language input of the user. The system design comprises four modules: i) input- which takes voice and handwritten list image input from the user; ii) processing- natural language processing of input data and converted to digital shopping list; iii) classification-list items classified into respective categories using machine learning algorithms; iv) output - searching on e-commerce applications and adding to shopping cart. The design proposed utilizes natural languages to communicate with the user thus enhancing their shopping experience. Google cloud speech recognition and Tesseract optical character recognition (OCR) for natural language processing have been utilized in the prototype along with support vector machine classifier for categorization.